The Effective Commands Used by the Teacher in English Teaching at SMP Lab Undiksha - Indrayani, I Gusti Ayu Diah; Utami, Ida Ayu Made Istri; Pratiwi, Ni Putu Astiti (International Journal of Language and Literature, 2022)
This study aimed at identify the types of disruptive behavior, identify the types of commands given by an English teacher, and analyze how the effective commands are given to students with disruptive behavior at SMP Lab UndikshaSingaraja. This study was a case study research. The method used in this study was descriptive qualitative method. The data were collected through filling observation sheet, distributing questionnaire, and conducting interview then analyzed by the researcher so that the researcher was able to draw and integrate ideas to create the conclusion. The result of this study revealed that students’ disruptive behavior that appeared during the teaching and learning process could be categorized as The Immature, The Well to Do, The Mountain Climber and The Game Player, furthermore. In overcoming those disruptive behaviors the teacher used several types of commands such as Others Commands, Don’t Commands, Regular Commands, Question Commands, Indirect Commands, Interrogations Commands, Stop Command, and Negative Commands. From those commands, thirteen times commands that appeared were categorized effective.